Retratos femininos na poesia de Camões - Marnoto, Rita (2011)
(2011). Petrarquismo em Camões. In Vítor Aguiar e Silva (Ed.), Dicionário de Luís de Camões (679-688). Lisboa: Caminho. IBSN 978 972 21 2146 0